FORMAÇÃO CONTINUADA DE PROFESSORES ALFABETIZADORES: UMA ANÁLISE CRÍTICA DO PROGRAMA PRÓ-LETRAMENTO - Alferes, Marcia Aparecida (2009)
This Dissertation presents an analysis of the formulation and management of the Program "Pró-Letramento", implemented by the Brazilian Federal government in 2005. The investigated program is an in-service teacher training for primary school teachers in Literacy and Mathematics. The research aims at investigating, in a critical perspective, the main aspects related to the conception and management of this program; the conceptions underpinning its contents and verify to what extent and in which perspective this program has contributed to meeting the requirements that led to its formulation. The theoretical framework of the research is the policy cycle approach (Bowe et al, 1992; Ball, 1994) and also contributions from authors who discuss the literacy process as well as the role of the school and the school knowledge in a critical perspective (Soares, 1998, 2002; Duarte, 2006; Frigotto, 1989; Libâneo, 2006). The research involved the following strategies of data collection: a) analysis of official documents and writing texts used in the program; b) interview with a pedagogic coordinator of the Program; c) fieldwork carried out in Garuva Town, Santa Catarina State, Brazil consisted of interviews with tutors, sessions of observation of the study meetings and questionnaire administered to primary school teachers who attended the study meetings of the program; d) observation of an appraisal seminar; and e)questionnaire administered to primary schools teachers based on different Brazilian states.The main conclusions are the following: a) The Pró-Letramento is a necessary intervention to the Brazilian educational context and display well designed strategies of implementation and partnership; b) in general, the tutors and the primary school teachers who have attended the study meetings consider that the Program is suitable as it offers consistent theoretical and practical aspects of the literacy process and has contributed to the improvement of the pedagogical practice in literacy classes; c) the program investigated focuses on a specific aspect (in-service teacher training in literacy and mathematics) and emphasizes the teacher's work on an individual basis. It argues that the Pró-Letramento is a necessary initiative, but not enough to construct an effective promotion of the quality of education offered to the working class families, which requires the implementation of other policies more far reaching than inservice teacher training strategies such as: adequate infrastructure of the schools, satisfactory teachers working conditions, participative strategies of pedagogic projects, the use of evaluation data for planning necessary interventions, among others.